Can D-Dimer Measurement Reduce the Frequency of Radiological Assessment in Patients Receiving Palliative Imatinib for Gastrointestinal Stromal Tumor (GIST)?. (14th September 2015) - Afshar, Mehran; Hamilton, Patrick; Seligmann, Jenny; Lord, Simon; Baxter, Paul; Marples, Maria; Stark, Dan; Hall, Peter S.
ABSTRACT: Imatinib therapy has improved outcomes in advanced GISTs. Current guidelines suggest monitoring with CT scanning every 12 weeks. There are no validated biomarkers to assist disease evaluation. We identified 50 patients treated with imatinib for GIST in a single tertiary center. We assessed the prognostic value of D-dimers by Cox regression, and the utility as a biomarker for radiological progression (rPD) using receiver-operator curve (ROC) analysis. In asymptomatic patients with D-dimer levels <1, 000 and falling levels, the negative predictive value for rPD was 92%. D-dimers may reduce the burden of CT scanning in a proportion of patients in this setting.